Formulation and Optimization of Aripiprazole-Loaded Nanostructured Lipid Carriers for Nose-to-Brain Delivery - Albaqshi, Layla; Singh, Amanjot; Khan, Shahzad; Kumar, Manish; Kour, Jagpreet; Pottathil, Shinu; Aldhubiab, Bandar; Tiwari, Abhishek; Nair, Anroop B (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Low bioavailability, highly variable blood levels and poor clinical efficacy of Aripiprazole (ARP) are primarily linked to its hydrophobic nature. This investigation focused on the formulation of ARP loaded Nanostructured Lipid Carriers (NLCs) incorporated in thermoreversible in situ intranasal gel for brain delivery. Materials and Methods: The high-speed homogenization method was used to formulate ARP loaded NLCs. A factorial design was utilized to optimize the particle size, entrapment efficiency and drug release of NLCs by selecting Tween 80 as a surfactant and stearic acid and castor oil as solid and liquid lipids, respectively. The ARP loaded NLCs thermoreversible in situ gel was fabricated using Poloxamer 407 as a phase transition agent and carbopol 940 as a mucoadhesive agent. The gel formulation was characterized for various pharmaceutical properties and nasal ciliotoxicity. Results: The optimized NLC (Z7) had nano size (~150 nm), good entrapment efficiency (~93%) and higher drug release (~75% in 12 hr). The formulated thermoreversible in situ gel (Z2 G) showed ideal gelling temperature, gel strength, and pH suitable for nasal use in addition to steady drug release and greater permeation. The toxicity study data revealed that the gel is safe for intranasal application. Conclusion: The prepared thermoreversible in situ gel of ARP loaded NLCs showed excellent potential for intranasal use and can be a feasible alternative to oral therapy in schizophrenia.
Keywords: Schizophrenia; Aripiprazole; Optimization; Poloxamer; Thermoreversible gel; Intranasal